ANALYSIS OF STRUCTURE OF BACKGROUND OF STUDENTS’ FINAL PROJECT - Mohammad Febryanto (STKIP Siliwangi, 2020)
Research must pay attention to the background of the research. The research background provides all the illustrations for the research paper. This study, therefore, aims to investigate the structure of the background of the students’ final project by looking at the moves and steps. Descriptive qualitative was used as a research method. In this study, there were 9 (nine) students' final project used as research objects. The data collection technique used was the document analysis. The results showed that moves 1 establishing a research territory and move 3 Occupying the niche found in the background of the students’ final project. Steps contained in move 1 were steps 1 and 3, namely making topic generalization by providing background information about the topic and reviewing an item of previous research by introducing and reviewing the results of research previously in the area. The step-in move 3 was the outlining purposes.